A Study of Epidemiological Surveillance System for Pulmonary Tuberculosis at the Public Health Center Bombana Regency - Bethan, Bari Azis (Miracle Journal of Public Health, 2022)
The achievement rate of finding patients with Pulmonary Tuberculosis in Bombana Regency in 2020 only 21,8%, so it has not reached the national target. This is partly because there are problems with the TB surveillance system. This was because there were problems with the TB surveillance system. This study aimed to determine the description of TB surveillance personnel, health human resources input system, infrastructure/facilities, methods, and funding at the Public Health Center (PHC) in the Bombana Regency. The type of study was descriptive. The sample in this study consisted 22 of the TB surveillance personnel at the PHC and TB surveillance personnel. Data collection used interviews and documentation. The data analysis was done descriptively. The results showed that from 22 PHC there were 40.91% tuberculosis surveillance personnel with an epidemiological background, 90.91% PHC with human resource according to the guidelines. PHC have complete infrastructure of 81.82%, and 95.45% of PHC have implemented tuberculosis surveillance methods according to standards and 100% of PHC have good funding. The conclusion of this research is that the facilities are complete, as well as the implementation and funding are quite good, the surveillance staff is according to the guidelines but still less than the type of implementing staff. Suggestions to the puskesmas to recruit surveillance personnel with an epidemiological background.